2019
DOI: 10.1111/cfs.12676
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining child welfare outcomes: Learning from Family Group Conferencing

Abstract: This article reports on a qualitative study, which sought to retrospectively understand the contribution family group conferencing (FGC) makes to longer‐term outcomes for children at risk of entering State care and their families. Eleven case examples of FGC were studied from five local government areas across Scotland. Each example included the perspectives of different stakeholders in the process: children, their parents/carers and extended family (n = 32), and professionals (n = 28) involved with them. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It was while interviewing young people for this research project that respondents also discussed their experiences of social work more generally, and it is this evidence that this paper explores. As such, while the research focused on FGC discussion in this paper does not explicitly link or make conclusions about the FGC process for young people and adult family members-this is done elsewhere (see Mitchell, 2019Mitchell, , 2021.…”
Section: Recognition and Misrecognition In Social Work Practicementioning
confidence: 99%
See 2 more Smart Citations
“…It was while interviewing young people for this research project that respondents also discussed their experiences of social work more generally, and it is this evidence that this paper explores. As such, while the research focused on FGC discussion in this paper does not explicitly link or make conclusions about the FGC process for young people and adult family members-this is done elsewhere (see Mitchell, 2019Mitchell, , 2021.…”
Section: Recognition and Misrecognition In Social Work Practicementioning
confidence: 99%
“…Please note, while the focus of the research was Family Group Conferencing this paper is wider—exploring children and young people's experience of social work rather than discussing the FGC process itself. Findings from original study on outcomes for children at risk of being accommodated by the state and family members involved in Family Group Conferencing are published elsewhere (see Mitchell, 2019; Mitchell, 2021). Key concepts of partnership and recognition in social work practice are discussed before summarizing the research methodology and limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of the profession, the relationships between social workers and service users have been seen to be at the centre of good social work practice (Trevithick, 2003). The relationship component of social work has been described by seminal figures as the 'soul' (Biestek, 1957), the 'heart ' (Perlman (1979), and the 'major determinant' (Hollis, 1970) of practice (Coady, 1993, p. 291), with contemporary authors also noting its key underlying role (Bryan et al, 2016;Colleagues and Authors own, 2019;Hood et al, 2019;Mitchell, 2020). Social work relationships are in fact both multifaceted and multiple 'with individuals, between individuals, with individuals in groups, with individuals and organisations, and between organisations' (O' Leary et al, 2013, p. 136).…”
Section: Social Work and Relationshipsmentioning
confidence: 99%
“…For example, in one study examining the social worker's ability to make and sustain relationships both with parents and with their children it was observed that: '… it was their relationship with their particular social worker that parents were to return to again and again during the course of interviews' (Author's own and colleague (2004, p. 217). Research has identified the core qualities that service users value in social workers that assist positive relationship development; these include, reliability, honesty, respect, effective communication and recognition of their innate worth and position (Devaney and Dolan, 2017;Drake, 1994;Mitchell, 2020;Platt, 2012;Toros et al, 2018;Trevithick, 2003). The ability to treat the service user as an individual person in their own right (Turney, 2012), as 'unique' rather than as a case or a number (Drake, 1994, p. 601), or than simply as a member of a category (Dybicz, 2012), also being regarded as essential.…”
Section: Social Work and Relationshipsmentioning
confidence: 99%